Parámetros distéticos, porcentaje de grasa y estado nutricional de estudiantes universitarios de bromatología y nutrición humana UNAP, 2019 - Sancho Murrieta, Maria Ines (2022)
The research was developed in order to collect data on the dietary parameters, percentage of fat and nutritional status of university students of the professional school of Bromatology and Human Nutrition of the UNAP enrolled in the academic year 2019. The research is of a non- experimental, descriptive correlational, cross-sectional; with a sample of 190 students; Instruments such as a survey of eating habits, a nutritional evaluation sheet, and fat percentage were used, which collected data on food, nutritional status was determined by BMI, and for the percentage of fat, the measurement of Skin folds. It was found that 76.3%, 15.8%, healthy and 7.9% unhealthy habits; Likewise, it was identified that 74.7% have a normal fat percentage, 19.0% have an obese fat percentage, and 6.3% have an overweight fat percentage; the nutritional status of the study sample 88.9% have normal nutritional status, 10.0% overweight, and 1.1% obesity. It was also evidenced at a confidence level of 95%, that there is a high statistically significant correlation (p < 0.05), Pearson's coefficient (0.709) between body fat and nutritional status according to BMI, with a significance value two-sided p = 0.000. The study also says that there is no statistically significant relationship (p < 0.05), Pearson's coefficient (0.052), between eating habits and nutritional status according to BMI, with a value of bilateral significance p = 0.479.